Study of the Effect of Electric Current Strength and Magnet Height Distance with Belt Three Disc Magnetic Separator on Middling Reprocessing Results from Processing Minerals at PT Timah Tbk - Annisa Makarim; Sudaryanto Sudaryanto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This study aims to reprocess middlings from the mineral processing process carried out at PT Timah Tbk which still contains cassiterite minerals using a three disc magnetic separator tool with variations in electric current strength and distance between the height of the magnet and the belt. Sn content will be analyzed using XRF. Variations in the strength of the electric current used are ranging from 0.3 A to 1.3 A which will be divided into 3 variations and variations in the height distance of the magnet with the belt used, namely 0.7, 1 and 1.3 cm. This research was carried out 9 times of testing which will be sought for the optimum level and recovery produced. The results showed the distribution of tin distribution in each size fraction. In addition, the Sn content and Sn recovery produced also varied for each test variation. The highest Sn content (%), 27.1%, was obtained in the test with the highest electric current strength variation and the smallest magnet height distance. Meanwhile, the highest recovery of 85.12% was obtained in the test with the smallest electric current strength and the largest magnetic height distance. Based on the results of the study, the higher the electric current strength used, the higher the Sn content obtained, but the lower the Sn recovery obtained. Meanwhile, the higher the height distance of the magnet with the belt used, the lower the Sn content obtained but the higher the Sn recovery obtained. As well as for the optimum levels and recovery obtained in research using strong electric current and the height distance of the magnet with a medium belt with Sn content of 12.2% and Sn recovery of 54.67%.